MEMPERKUAT KEPUTUSAN PEMBELIAN JASA URBANCUT BARBERSHOP MELALUI MEDIASI CITRA TOKO - Alala, Legazea Syifa; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2017)
This study aims to strengthen purchase decision Urbancut barbershop services. Starting from sales decline problem of Urbancut services and created a research question: